Bastion - Lackey, Mercedes (Lackey, Mercedes. Collegium chronicles, 2013)
Mags travels to the Bastion in search of who his parents were and a possible explanation about why he is being pursued by Valdemar's enemies in the fifth and final volume of the series following Redoubt.